Національні проблеми виконання міжнародних зобов’язань в сфері розвитку людського капіталу - Березянко, Тамара Володимирівна (My University, 2020)
Людський капітал, темпи та напрямки його розвитку визнано в світі основним драйвером розвитку національної та світової економіки. Для здійснення науково-технічного прориву, вирівнювання темпів розвитку національної економіки згідно світовим тенденціям людський капітал має бути створено, накопичено та забезпечено його постійний розвиток державними інституціями. Стан розвитку людського ресурсу в плані формування стійкого за структурою людського капіталу використав попередній ґрунт для розвитку і знаходиться у стані невизначеності. Запущені в національному суспільстві реформи, що безпосередньо впливають на якість людського капіталу та покликані створити фундамент до його розвитку, ефекту не приносять, навіть не зважаючи на іноземний донорський управлінський десант. Ця стаття призначена виявити основні дисонанси програмного та фактичного розвитку людського капіталу, та виявити розбіжності між потребами національного суспільства, напрямками адаптації та впровадженими управлінськими конструкціями. Human capital, the pace and direction of its development is recognized in the world as the main driver of national and world economy. In order to make a scientific and technological breakthrough, to equalize the pace of development of the national economy in accordance with global trends, human capital must be created, accumulated and ensured by its continuous development by the state institutions. According to international experts, only 5% of countries that have embarked on a path adapted to global development trends have a chance to enter the circle of developed countries. The rest will remain recipients of progressive achievements or lifelong providers of cheap resources. Human capital as a vehicle for the development of national society is present in the Government's medium-term action plans. However, this presence is formal and is reduced to health indicators that are constantly deteriorating. capital as a leading factor in the development of economy and society. The standard of living is significantly reduced compared to pre-reform times, the labor and social activity of the population has worsened, labor migration has become important ekspotrnyh performance factor of the country, indicating a lack of national direction. Clearly, this situation leads to the identification of critical points and finding mechanisms to curb negative processes in the development of human capital. The state of human resource development in terms of the formation of a stable human capital structure used the previous ground for development and is in a state of uncertainty. The reforms launched in the national society, which directly affect the quality of human capital and are intended to create a foundation for its development, do not bring any effect, notwithstanding the foreign donor management. This article is intended to identify major discrepancies in programmatic and actual human capital development, and to identify differences between the needs of national society, the areas of adaptation, and the management structures that have been implemented.
Keywords: state policy; methodology; саміт; людський капітал; державна політика; методологія; human capital; summit; кафедра економіки праці та менеджменту